Capture, Culture and Release of Postlarvae Fishes: Proof-of-Concept as a Tool Approach to Support Reef Management - Cortés-Useche, Camilo; Reyes-Gamboa, Williams; Cabrera-Pérez, José Luís; Calle-Triviño, Johanna; Cerón-Flores, Ana; Raigoza-Figueras, Rodolfo; Yathiraj, Roshni; Arias-González, Jesús Ernesto (Frontiers in Marine Science, 2021)
The changing world presents negative impacts on marine ecosystems and has led to the development of diversified tools to support reef restoration. Harnessing restoration to achieve success needs innovative techniques that also address the restoration of reef fish assemblages, contributing to the conservation of biodiversity and ecosystem functions, as well as tackle the cost-effectiveness through impact driven solutions. Here, we propose a proof of concept for enhancing fish populations on reefs using: 1) post-larvae capture, 2) aquarium-culture and 3) release to reef sites. We conducted field studies in the Mexican Caribbean to analyze for the first-time, the possibility of using the capture and aquarium-culture of post-larvae fish species and release of juveniles as a tool for the potential recovery of reef biodiversity resilience. We tested the potential of post-larvae capture using two distinct night light traps (BOX and C.A.R.E.) in three sampling sites with different distances from shoreline and depth. We collected 748 post-larvae reef fishes from 8 orders, 20 families, and 40 species. Acanthuridae, Pomacentridae, Monacanthidae, and Tetraodontidae comprised the highest species number of post-larvae families. We also set-up a pilot release experiment with S. partitus using two trials (32 and 1 day after capture) and propose analysis to determine appropriate reef sites to release the cultured juveniles and to aid ecological planning. We present the results of the pilot release experiment with Stegastes partitus, showing that there is a positive effect in survivorship during the capture (80%) and release (76-100%) procedures into suitable habitat and good chance that more studies will bring novelty to the field. Although trails carried out with more species relevant to restoration will be needed. The use of these techniques can be a great opportunity to improve research of restoration efforts in the Caribbean region with fish-depleted coral reefs with vulnerable food webs, especially at local scales and supporting other management strategies.